Self-Healing Data Pipelines Using Predictive Monitoring: Architectures, Techniques, and Applications for Autonomous Data Systems - Srinivasa Rao Seetala (International Journal of Scientific Research in Science and Technology, 2026)
Modern data-driven systems rely heavily on complex, distributed data pipelines that ingest, process, transform, and deliver data across heterogeneous environments at scale. As organizations increasingly depend on real-time analytics, AI/ML models, and data-driven decision-making, the reliability of these pipelines becomes mission-critical. However, such systems are inherently vulnerable to a wide range of failures, including schema drift, data anomalies, upstream dependency changes, infrastructure instability, network latency, and rapidly evolving workloads. Traditional reactive monitoring approaches primarily based on static thresholds and alerting are insufficient to ensure resilience, as they detect issues only after failures have already impacted downstream systems. To address these limitations, this paper proposes a self-healing data pipeline architecture that leverages predictive monitoring techniques, integrating machine learning-based anomaly detection, automated root cause analysis, intelligent remediation strategies, and continuous observability across the data lifecycle. By incorporating AIOps principles with adaptive ETL workflows, the architecture enables pipelines to anticipate potential failures, dynamically adjust to changing conditions, and autonomously recover from disruptions with minimal human intervention. Furthermore, the system utilizes historical pipeline behavior, metadata, and real-time telemetry to continuously refine its predictive capabilities, thereby improving accuracy over time. Experimental insights and recent studies indicate that such predictive and self-healing mechanisms can significantly reduce failure rates, minimize downtime, enhance data quality, and improve overall system efficiency, ultimately enabling organizations to build robust, scalable, and intelligent data infrastructure capable of supporting modern digital ecosystems.
Keywords: Self-healing systems; data pipelines; predictive monitoring; anomaly detection; AIOps; ETL automation; data observability; machine learning; fault tolerance; data quality